The Influence of the Ethnoscience-Based Problem Based Learning Model on Science Learning Outcomes Reviewed from Students' Cognitive Styles - Ni Luh Nopi Pujiani; Ketut Suma; I Nyoman Jampel (Jurnal Ilmiah Sekolah Dasar, 2026)
Low science and social studies (IPAS) learning outcomes among elementary school students remain a persistent problem, particularly due to learning practices that are less contextual and have not fully accommodated differences in students’ cognitive styles. As a result, students often experience difficulties in understanding abstract IPAS concepts meaningfully. This study aimed to analyze the effect of an ethnoscience-based Problem Based Learning (PBL) model on IPAS learning outcomes in terms of students’ cognitive styles. This research employed a quantitative approach using a quasi-experimental method with a pretest–posttest control group design. The research subjects were 87 fourth-grade students from public elementary schools in Cluster V, Kintamani District, who were selected through random sampling and assigned to experimental and control groups. Data were collected using an IPAS learning outcomes test that had been validated and tested for reliability. Data analysis was conducted using two-way Analysis of Covariance (ANCOVA) to examine the effects of the learning model, cognitive style, and their interaction on learning outcomes, followed by Scheffe’s post hoc test. The results showed that the ethnoscience-based PBL model had a significant effect on students’ IPAS learning outcomes. In addition, a significant interaction was found between the learning model and cognitive style. Students with a reflective cognitive style achieved higher learning outcomes than those with an impulsive cognitive style. These findings indicate that ethnoscience-based PBL is effective in improving IPAS learning outcomes when students’ cognitive characteristics are taken into account.